Analisis kemampuan menyelesaikan soal HOTS model TIMSS dan kepercayaan diri siswa sekolah menengah pertama - Gity Wulang Mandini; Hartono Hartono (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2018)
Penelitian ini bertujuan menganalisis kemampuan siswa SMP di Kabupaten Wonosobo dalam menyelesaikan soal HOTS model TIMSS dan mendeskripsikan kepercayaan diri siswa SMP di Kabupaten Wonosobo. Penelitian ini termasuk penelitian survei. Populasi penelitian adalah seluruh siswa kelas VIII SMP di Kabupaten Wonosobo pada tahun pelajaran 2016/2017. Pengambilan sampel menggunakan metode stratified proportional random sampling dan diperoleh 99 siswa sebagai sampel yang terbagi dalam 4 sekolah, yaitu 1 sekolah kategori tinggi, 2 sekolah kategori sedang, dan 1 sekolah kategori rendah. Hasil penelitian menunjukkan kemampuan menyelesaikan soal HOTS model TIMSS siswa SMP Kabupaten Wonosobo dalam kategori sedang (85,9%). Selanjutnya dilihat untuk masing-masing indikator dari soal HOTS model TIMSS, indikator memadukan/ mensintesis, menganalisis, memberikan alasan, dan menyelesaikan masalah non-rutin berada pada kategori sedang, hanya terdapat 1 indikator yang berada pada kategori rendah yaitu menggeneralisasi. Sedangkan untuk kepercayaan diri siswa SMP di Kabupaten Wonosobo berada pada kategori sedang (56,6%). Bila dilihat untuk masing-masing aspek, bahwa aspek keyakinan akan kemampuan diri, optimis, objektif, dan bertanggung jawab berada pada kategori sedang, untuk aspek rasional dan realistis berada pada kategori rendah An analysis of junior high school students’ability in solving HOTS model TIMSS and self-confidence AbstractThe purpose of this study were to analyze the ability of junior high school students in Wonosobo to solve the HOTS model TIMSS problem and to describe the self-confidence of junior high school students in Wonosobo. This study was a survey. The population was all 8th grade of Wonosobo Junior High School in the academic year 2016/2017. Sampling used was stratified proportional random sampling method. The samples consisted of 99 students from 4 representative schools, namely 1 school for high category, 2 schools for medium cateogry, and 1school for low category. The results showed that the ability to solve the HOTS model TIMSS problem of junior high school students in Wonosobo was in the medium category (85.9%). Furthermore, for each indicator of HOTS model TIMSS problem, found that indicators integrate/ synthesize, analyze, justify, and solve non-routine problems were in medium category, there was only 1 indicator that in low category that is generalization. As for self-confidence of junior high school students in Wonosobo was in medium category (56.6%). When viewed from each aspects, aspect of belief in self-ability, optimist, objective, and responsible were in medium category, aspect of rational and realisticis was in low category.